Taxonomy and Diversity of Vascular Plant Species in Cherangani Forest of Marakwet West in Kenya - Makokha, J. O.; Njenga, E. W.; Malombe, I.; Wanjohi, B. K. (Africa Environmental Review Journal, 2022)
The availability of accurate and sufficient information on plant taxonomic groups and similarity measures is crucial for making informed conservation decisions. In many forests, due to human population pressure, many species face the risk of extinction, some of which could be possessing solutions to numerous problems facing mankind. However, due to inaccessibility caused by extreme isolation and harsh conditions, little research has been done in this field on plants in Cherangani forest station. This study focused on the numbers of various plant taxa and their distribution in Cherangani done in blocks with a view of developing a management database. Standard botanical inventory and Herbarium protocols were used and analysed using a Microsoft Excel spreadsheet. Eight hundred and fifteen (815) species in 129 families and 450 genera respectively were identified. This is an indication that this flora is one of the richest in the country hence a priority conservation spot. Additionally, the blocks vary in species numbers and growth forms, therefore, necessitating varied management.